Impact of annular and supra-annular CoreValve deployment locations on aortic and coronary artery hemodynamics. (October 2018) - Kandail, Harkamaljot S.; Trivedi, Setu D.; Shaikh, Armaan C.; Bajwa, Tanvir K.; O'Hair, Daniel P.; Jahangir, Arshad; LaDisa, John F.
Abstract: CoreValve is widely used in transcatheter aortic valve replacement, but the impact of its deployment location on hemodynamics is unexplored despite a potential role in subsequent aortic and coronary artery pathologies. The objectives of this investigation were to perform fluid-structure interaction (FSI) simulations for a 29 mm CoreValve deployed in annular vs supra-annular locations, and characterize resulting hemodynamics including velocity and wall shear stress (WSS). Patient-specific geometry was reconstructed from computed tomography scans and CoreValve was deployed using a finite element approach. FSI simulations were then performed using a boundary conforming method and realistic boundary conditions. Results showed that CoreValve deployment location impacts hemodynamics in the ascending aorta and flow patterns in the coronary arteries. During peak-systole, annularly deployed CoreValve produced a jet-like flow structure impinging on the outer-curvature of the ascending aorta. Supra-annularly deployed CoreValve having a lateral tilt of 10° led to a more centered jet impinging further downstream. At mid-systole, valve leaflets of the annularly deployed CoreValve closed asymmetrically leading to disorganized flow patterns in the ascending aorta vs those from the supra-annular position. Supra-annularly deployed CoreValve also led to high-velocity para-valvular flow supplying the coronary arteries. CoreValve in the supra-annular position significantly ( P  < 0.05) elevated WSS within the first few diameters of both coronary arteries as compared to the annular position for many time points quantified. These results afforded by the advanced simulation methods may have important clinical implications given the role of aortic hemodynamics in dilation and the pro-atherogenic nature of WSS alterations in the coronary arteries.